EMPHASIS AND EXPRESSIVITY IN THE DAILY SPEECH OF NEPALI-ENGLISH BILINGUALS - Vasseur, Julian (PALIMPSEST / ПАЛИМПСЕСТ, 2019)
Bilingual conversations contain numerous possibilities for expressive communication. A significant proportion of Nepali speakers living in urban areas and belonging to the latest generations have received an English-medium education and use Nepali and English together in their daily interactions. Nepali and English are both used as lingua francas nowadays in a growing number of contexts in urban areas in Nepal. This is especially the case in TV and radio entertainment broadcasts targeted at a young audience. In such programs, the participants constantly alternate the two languages for expressive purposes. By doing so, they display that they belong to a modern, urban, professionally successful part of global society. The aim of this article is to present a summary of the sociolinguistic context and the role of English in Nepal today, as well as a selection of means to convey semantic emphasis both in Nepali and in Nepali-English bilingual interactions in the media. This leads us to believe that Nepali speakers, when adding in English segments to their daily speech, tend to reinforce the expressive elements already at their disposal in Nepali.